2010
DOI: 10.2174/1875692111008010025
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing Stem Cell Research and Therapy: The Arduous Road Ahead or Missed Opportunity?

Abstract: The euphoria of stem cell therapy has diminished, allowing scientists, clinicians and the general public to seriously re-examine how and what types of stem cells would effectively repair damaged tissue, prevent further tissue damage and/or replace lost cells. Importantly, there is a growing recognition that there are substantial person-to-person differences in the outcome of stem cell therapy. Even though the small molecule pharmaceuticals have long remained a primary focus of the personalized medicine researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…For those applications, the source of the cells will be a major hurdle because the cells should be healthy and may need to be isolated before the disease state of the patient. These patient‐derived stem cells might be susceptible to contamination, genetic modifications, or might already possess disease‐causing mutations that are not apparent at the time of transplantation, thereby compromising the outcome of therapy 35. Such applications will pose a challenge, even from a process perspective.…”
Section: Stem Cell Applicationsmentioning
confidence: 99%
“…For those applications, the source of the cells will be a major hurdle because the cells should be healthy and may need to be isolated before the disease state of the patient. These patient‐derived stem cells might be susceptible to contamination, genetic modifications, or might already possess disease‐causing mutations that are not apparent at the time of transplantation, thereby compromising the outcome of therapy 35. Such applications will pose a challenge, even from a process perspective.…”
Section: Stem Cell Applicationsmentioning
confidence: 99%
“…Autologous transplantations employ a patients own tissue and thus present no tissue incompatibility between the donor and the host due to a lack of stimulation of the immune response. However, in cases where there is a need for immediate treatment with stem cells, it will not be practical to wait for ex vivo expansion and re-transplantation of autologous stem cells [30]. Moreover, because the functional impairment of stem and progenitor-derived cells harvested from patients with chronic heart failure may limit the efficiency of autologous stem cell treatment.…”
Section: Transplantation Of Allogenic Derived Stem Cellsmentioning
confidence: 99%
“…Several humoral factors govern and control these processes [36]. Thus variations among microenvironments which could be influenced by the patient’s background as well as other underlying clinical disorders might be relevant for the functions of stem cells in each different host [30]. The composition of the microenvironment and the presence of certain soluble factors are major determinants for proliferation, differentiation and homing of applied stem or progenitor cells.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, autologous iPSCs derived from the patient's somatic cells are considered a potentially landmark solution. Even in a situation where an immediate treatment is unnecessary, a therapeutic strategy to wait for ex vivo reprogramming and expansion with the subsequent retransplantation of autologous stem cells may not be financially and clinically feasible [28]. Recently, Zhao et al reported that the cells differentiated from iPSCs can induce Tcell-dependent immune responses in syngeneic recipients [29].…”
mentioning
confidence: 99%